OPTIMALISASI PENGENDALIAN HAMA TIKUS MELALUI PROGRAM BINA DESA DENGAN APLIKASI LETUPAN EMPOS TIKUS DI LAHAN BASAH - Muslimin Sepe; Wahyu Bimas Abadi; Jubaidah Jubaidah; Siti Maulydia Rahmah; Echa Aulia Listiaweni; Rizky Amelia Safitri; Jannatul Fatwa; M. Ridho Putra Perdana; Muhammad Fadhil Fitrian; Muhammad Husein Nafarin Aruba; Muhammad Farizh Faqih; Rachmad Guntur Saputra (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Rural Community Development program (Bina Desa) at Universitas Lambung Mangkurat is an implementation of the Integrated Learning Activity Mobility (MKBT) framework, an expansion of the Merdeka Belajar Kampus Merdeka (MBKM) policy. This program aims to facilitate cross-disciplinary and international learning experiences, bridging the gap between theoretical academic discourse and empirical field practice to enhance students' global competitiveness. This study details a community service initiative conducted in Astambul District, focusing on rodent pest management through the application of "Letupan Empos Tikus" (LETI) technology, in collaboration with the Sinar Padi Farmers Group of Sungai Tuan Ilir. The primary objective was to provide students with experiential learning opportunities in applying specialized agricultural knowledge to address local community exigencies. The methodology employed a phased participatory approach, beginning with site surveys and problem identification regarding rodent infestations, followed by educational outreach, farmer empowerment, intensive mentoring, and systematic monitoring and evaluation. Results indicate high levels of engagement from the farming community. The dissemination of LETI technology was successfully executed with the strategic support of the Agricultural Extension Center (BPP) of Astambul, local Field Extension Officers (PPL), and Pest Observation Officers (POPT). The program yielded significant mutual benefits: enhancing students' practical competencies while providing the farming group with effective pest control solutions. Based on these outcomes, the institutionalization of this program on an annual basis is highly recommended to ensure sustainable agricultural development and academic integration.